(untitled) - Lavenda, Robert H. (Boston, Mass., 2007)
This very concise, accurate introduction to the basic ideas and practices of contemporary cultural anthropology is designed to address the needs of anthropology professors who make extensive use of ethnographies and other supplementary readings in their courses. Not a standard textbook, Core Concepts in Cultural Anthropology functions as a thorough annotated bibliography of the terms and concepts that anthropologists use in their work; its conceptual framework prepares students to read ethnography more effectively, with less misunderstanding
Keywords: Ethnology,Nhân chủng học